Friction damping and forced-response of vibrating structures: An insight into model validation - Umer, Muhammad; Gastaldi, Chiara; Botto, Daniele (International journal of solids and structures, 2020)
Dry friction is widely incorporated in turbomachinery, in the form of under-platform dampers, to limit vibrations at resonance and reduce risks of high-cycle fatigue failures. Most of the test rigs that were used to investigate the behavior of under-platform dampers aim at evaluating the damper performance in terms of reduction of forced-response amplitude in blades. This approach could be insufficient to understand local nonlinearities in the contact and the influence of dampers on blade dynamics. A recently developed test rig provides the authors with an unprecedented set of information. It is capable to measure contact forces and relative displacements between dampers and blade in addition to the overall blade dynamic response. This controlled environment, together with an effective model of the blade/dampers system, is used to provide an insight into the subject of model validation. The presented experimental and numerical study of the damper is used to highlight the relevance of an accurate representation of the constraints induced by friction contacts and to discuss the adequacy of state-of-the-art contact models.